The United Nations Force Intervention Brigade: Wither the SADC/ICGLR Synchronised Peace Support Efforts in the Eastern Democratic Republic of Congo Recurring Conflict? - Rugeje, Engelbert Abel; Maeresera, Sadiki (Penerbit Universiti Utara Malaysia, 2016)
From the time it deployed in the eastern DRC in 2013 up to the first quarter of 2016, arguably no much tangible progress has been made by the United Nations Force Intervention Brigade (UN FIB).The security situation in eastern Congo continues to be unstable.This instability has serious direct security threats and spillover effects on respective neighbouring countries that are either part of the Southern African Development Community (SADC) or the International Conference on the Great Lakes Region (ICGLR).There are certain constraints that the FIB has continued to encounter in the context of regional and international political and strategic dynamics surrounding eastern Congo recurring conflict. This paper argues that one of the contributing factors behind the challenges encountered by the UN Force is the fact that both the ICGLR and the SADC efforts at enhancing peace enforcement in the eastern DRC have been overshadowed by the self-interests of international actors. Arguably, this scenario has impacted negatively on the ICGLR/SADC synchronised efforts towards the effectiveness of the FIB.The paper makes some recommendations on how best to attain sustainable synergy between the ICGLR and SADC in order to enhance the strategic and operational efficiency and the effectiveness of the UN FIB in the eastern Congo conflict.